Досвід розрахунково-екпериментального оцінювання енергетичних показників будівлі школи - Настоящий, В. А.; Пашинський, В. А.; Пашинський, М. В.; Джирма, С. О.; Nastoiashchyi., V.; Pashynskyi, V.; Pashynskyi, M.; Dzhyrma, S. (НУВГП, 2020)
Висвітлена методика і результати оцінювання показників енергетичної ефективності будівлі школи з урахуванням теплових характеристик огороджувальних конструкцій, отриманих за даними вимірювань у процесі натурних обстежень. Проаналізовано вплив термомодернізації на клас енергетичної ефективності будівлі. During the examination, numerous damages of the outer wall cladding, unfilled seams between the wall blocks and poorly executed junction of window and door frames to a wall were revealed, where heat transfer is highly increased due to air leakage from the inside of the building. The actual values of the heat transfer resistance of walls and translucent structures, experimentally established using a thermohygrometer, do not meet the requirements of current standards. Examination of the outer walls and window blocks using a thermal imager revealed thermal anomalies that significantly reduce the thermal insulation characteristics of enclosure structures. It is noted that the use of technical devices makes it easy to detect thermal anomalies and to estimate the characteristics of enclosure structures. Based on the research results, an energy passport of the building was developed. The design value of specific energy consumption is 55.7 kW×h/m3. Taking into account the maximum value of 35 kW×h/m3 for educational institutions, that are a subject of thermal modernization, the building was examined and classified as energy efficiency class F. Design proposals have been developed for thermal modernization of the building by using ventilated facade systems with rockwool insulation. After thermal modernization, the specific energy consumption are reduced to 34.7 kW×h/m2, and the energy efficiency is improving to class C.
Experience of design and experimental evaluation of energy indicators of school building
Keywords: будівля; огороджувальні конструкції; обстеження; клас енергоефективності; building; enclosure structures; expertise; energy efficiency class